An Analysis of Teachers’ Grammatical Errors in Composing Summative Assessment - Yunus Gani; Sartin Miolo; Novriyanto Napu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
English is a challenging topic for Indonesian students since the English language is so different from the Indonesian language and one of the topics in English is grammar. However, sometimes language learners make grammatical errors and teachers are not an exception. This research focuses on the categories of grammatical errors found in the summative assessment composed by the MGMP teachers in Boalemo and their perceptions regarding the said error. This study employed descriptive qualitative method and utilized document and interview to collect the data. The techniques of data analysis are document and thematic analysis. After conducting this research, it is found that the most committed error by the participant is the error of omission, specifically omission of parts of speech and this error is caused mainly by the lack of quality control among the MGMP teachers. This research is intended to develop the study of teaching, specifically improving grammatical comprehension.